The Effect of the Teams Games Tournament Learning Model Assisted by Wheel of Math and Card Matching on Students' Mathematical Critical Thinking Skills in the Topic of Linear Equation Systems - Qausar, Haves; Hidayat, Amam Taufiq; Wani, Sinar (LPPM UNIMAL, 2025)
This study aims to understand the differentiation in critical thinking skills between students taught using the Teams Games Tournament (TGT) learning model assisted by Wheel of Math and Card Matching, and those taught using a conventional learning model on the topic of linear equation systems in Grade X at PDF Ulya Al-Huda Malikussaleh. The study employs a Quasi-Experimental methodology with the assistance of SPSS 21 software. Data collection techniques involve a test instrument in the form of an essay test consisting of five reliable questions. The hypothesis testing of the posttest results shows a significance score (2-tailed) < 0.05, specifically 0.021 < 0.05. Therefore, H‚ is rejected, indicating that the application of the TGT model has a significant effect on the learning outcomes of tenth-grade students at PDF Ulya Al-Huda Malikussaleh, Reulet Timur.